2016
DOI: 10.1186/s13071-016-1644-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of Orco and odorant receptors in odor recognition in Aedes albopictus

Abstract: BackgroundAedes albopictus is a globally invasive mosquito and a major vector of arboviruses, including dengue, Zika and Chikungunya. Olfactory-related behaviors, particularly host-seeking, offer opportunities to disrupt the disease-transmission process. A better understanding of odorant receptors (ORs) may assist in explaining host selection and location, and contribute to novel strategy of vector control.MethodsBased on previous prediction of 158 putative odorant receptors by Ae. albopictus genome analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 53 publications
(89 reference statements)
2
44
1
Order By: Relevance
“…The developmental and tissue-specific expression profiles of conventional odorant receptors, are highly distinct and species-specific; for example, AgOR1 is expressed specifically in female Anopheles gambiae [13] and AgOR4 is highly expressed in the antennae [14]. AalOR7, AalOR10, and AalOR88 were detected significantly and specifically in female antennae [15]. Among the 57 odorant receptor genes in Drosophila, 32 are specifically expressed in the antenna, with seven being exclusively expressed in the maxillary palp, and one in both the antenna and maxillary palp.…”
Section: Discussionmentioning
confidence: 99%
“…The developmental and tissue-specific expression profiles of conventional odorant receptors, are highly distinct and species-specific; for example, AgOR1 is expressed specifically in female Anopheles gambiae [13] and AgOR4 is highly expressed in the antennae [14]. AalOR7, AalOR10, and AalOR88 were detected significantly and specifically in female antennae [15]. Among the 57 odorant receptor genes in Drosophila, 32 are specifically expressed in the antenna, with seven being exclusively expressed in the maxillary palp, and one in both the antenna and maxillary palp.…”
Section: Discussionmentioning
confidence: 99%
“…Based on membrane topology analysis of the AcerOrc2 sequences, we showed that the CaM-binding domain residue in ICL2 was found to be highly conserved. This domain has been studied in Drosophila melanogaster 336 SAIKYWVER 344 (Mukunda et al, 2014) and in Aedes albopictus, 329 SAIKYWVER 337 (Liu et al, 2016), and this sequence conservation indicates that CaM activity in ICL2 plays a crucial functional role in the formation of functional ion channels by AcerOr2. In addition, the Tyr residue Y469 in AcerOr2 TM7 is conserved in B. mori (Y464) (Tatsuro et al, 2012) and L. lucorum (Y463) (Zhou et al, 2014) and has been confirmed to be critical for ion function, whereas conventional AcerOr1 does not have this sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental evidence suggested that mosquito ORs act as ligand-gated ion channels comprising of heteromeric complexes of two subunits [38,39]. One subunit is highly conserved and known as olfactory receptor co-receptors (Orco), and the other subunit is largely divergent in terms of number as well as amino acid sequences (Orx) [31,[40][41][42]. Pilot studies of the OR gene repertoire primarily in Drosophila melanogaster [35] and later in mosquitoes [42,43] suggest that despite having a limited number of ORs, mosquitoes can respond to an array of varied chemicals depending on the specific demand at different life cycle stages [44].…”
Section: Odorant Receptorsmentioning
confidence: 99%